Sufisme Syekh Nawawi dalam Tafsir Marâh Labîd - Kholilurrahman Kholilurrahman (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2019)
This paper examines whether there are possibilities of the teachings of Sufism as outlined in the tafsir book Marâh Labîd, Is there a correlation of Sheikh Nawawi's notes in Salâlim al-Fudlalâ 'with the interpretation of Marâh Labîd? The results of this analysis conclude whether there is a interpretation of Marâh Labîd as a book of interpretations patterned as Sufism or not. The Sufi Sheikh Nawawi al-Bantani, a multi-disciplinary cleric as Sayyid ‘Ulamâ’ al-Hijâz and Sufism expert. He is a practitioner and writer. His phenomenal work is Salâlim al-Fudlalâ € ™ Syarh Hidayah Al-Adzkiyâ € 'whose entire writing is written with al-Sarraj in al-Luma' definition of Sufism teachings in the book Salâlim al-Fudlalâ '. Popular works, Nashâ-ih al-bIbâd Syarh al-Munabbiht ‘Alâ al-Isti’dâd li Yawm al-Ma'âd, contain pure Sufism to improve morals to Allah, His Messenger, and others. One of his great works, namely Marâh Labîd is known as Tafsir al-Nawawi or al-Munir al-Tafsir Li Ma’alim al-Tanzil.